(3QjMGfg GdGdHG h RgQg GdMjGg GdOfjGs - (3GdNaGLj, GdeUQj, GdMfaj, TgGH GdOjf, CMeO Hf eMeO Hf YeQ, J (B1069(3g`s ((3eMeO Hf Ydj Hf TQa GdOjf Hf EHQGgje GdLQjSj GdCfUGQj GdTGaYjs)
(3ChdgG (B:s
(3MeOG def SQM Yjhf GdHUGFQ aj QjGV GdfYe agPg PNGFQ ef NHGjG GdRhGjG ajeG aj GdQLGd ef GdHbGjG JfaS GdOgQ HgG Yf faMI YfHQjI hgHJ HgG CfaGS fOjI fqOjI JfaS GdQhV aj GdCSMGQ s
(3BNQgG (B:s
(3hCeG GdCejQ CHh aQGS GHf MeOGf agh aGQS GdgjLGA hChMO GdHdZGA hGdaUMGA hdCHj ESMGb GdZRj ef bUjOI (B: (3LMhO aVjdI GdTYQGA Zj hJaNje GdeOjM ef GdQTGO Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\238s
(3EjVGM Gdecfhf (B1\605s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs